Software tools in didactics of mathematics - Dudzińska-Baryła, Renata; Kopańska-Bródka, Donata; Michalska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The use of software tools in the teaching process allows us to enrich the traditional methods. Graphics and animation complement the text and create positive associations related to the presented content. Recent research shows that using the visual methods in teaching leads to better scores obtained by students. The aim of the paper is to present the dynamic visualisations of selected concepts taught in mathematics and other “quantitative” subjects at university. Our dynamic visualisations can be used during lectures to help students to better understand difficult ideas and dependencies, for example the derivate of a function, the concept of fuzzy sets and the operations on these sets as well as the concept of the best solution in multi-objective programming problems. Visualisations of these issues are prepared in GeoGebra, which combines algebra and geometry and allows for the dynamic visualisation of concepts with a mathematical background.
Didactics of Mathematics, 2015, Nr 12 (16), s. 35-46
Keywords: visualisations; GeoGebra; multi-objective programming; fuzzy sets; derivative